How Important Is Geography in the Implementation of ESD in Schools Compared to Other Subjects? Findings of a Systematic Review of Empirical Studies - Hemmer, Ingrid; Wittlich, Christian; Schult, Bente (Journal of Geography Education, 2025)
This systematic review investigates the role of geography in the implementation of ESD compared to other subjects. Database searches and textual analysis yielded 33 publications in German and English, providing subject comparisons in terms of framework documents, curricula, teacher education, the school as a learning environment, and assessment. The results and the subsequent discussion demonstrated that geography plays a significant role in all areas, supporting its claim as a leading subject for ESD. The findings are substantiated by a strong alignment in disciplinary concepts, objectives, content, competencies, and methodologies. The conclusion outlines implications for future research and the implementation of ESD.
Keywords: geography, school, subject comparison, ESD implementation, systematic review